Dessiner d’après la bosse à Lyon - Sarah Betite (In Situ)
The first real art school in Lyon is the Free Drawing School, created in 1756. This school had to train both artists and draughtsmen who would be drawing flowers for the local silk industry. The École impériale des beaux-arts de Lyon was opened in 1807, next to the Fine Arts Museum at the Palais Saint-Pierre. After moving several times and undergoing a radical reorientation in the 1970s, the École nationale supérieure des beaux-arts de Lyon settled on Les Subsistances, next to the Quai Saint-Vincent. During the 19th and 20th centuries, many professional art teaching establishments were developed in Lyon, in addition to the School of Fine Arts. The plaster casts are first-class pedagogical tools for these teachings based on the academic model, but their origins, their number, their models and their distribution are now poorly known. However, there remains a gallery of hundreds of casts kept by the ENSBA. A part of it is now kept at the Musée des Moulages of the Lumière-University Lyon-2. This article aims to offer a preview of the material history of the plaster casts that were used in Lyon to teach drawing, and to understand their pedagogical and economical stakes. This study will allow on one hand us to count, localise and understand the origins of the existing vestiges for work of national heritage, and on the other, to evaluate the importance and the specificity of the Lyon collections on a wider scale.